Partnerstwo Wschodnie jako instrument polityki wschodniej UE? - Barabasz, Adam, Marcin Piechocki (Wydział Nauk Politycznych i Dziennikarstwa Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2012)
The Eastern Partnership as an element of the European Union’s Eastern policy Established on the initiative of Poland and Sweden, the Eastern Partnership encompasses sixstates located in the territory of the former USSR, namely Armenia, Azerbaijan, Georgia, Moldova, Ukraine and Belarus. The program was officially initiated in 2009 by offering its members such solutions as softening visa restrictions, the establishment of free trade zones and signing association agreements. One of the priorities of the Polish Presidency, the Eastern Partnership culminated in the summit held in Warsaw on September 29–30, 2011. While Poland sees this project as an opportunity for further enlargements, other member states are not unanimous about what character it should have. Should the Eastern Partnership constitute the eastern dimension of the European Neighborhood Policy, or just the advancement of democratic values without promising EU membership in return for their implementation. This influences the assessment of the Eastern Partnership upon its third year of operation, and of the activities of the Polish Government during the Presidency. Although cooperation between the EU and the countries of the Eastern Partnership was not significantly advanced, Donald Tusk’s Government succeeded in maintaining the EU’s interest in this topic among member states otherwise engrossed in the eurozone crisis.